2015
DOI: 10.1111/imr.12298
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligases Pellinos as regulators of pattern recognition receptor signaling and immune responses

Abstract: SUMMARY Pellinos are a family of E3 ubiquitin ligases discovered for their role in catalyzing K63-linked polyubiquitination of Pelle, an IL-1 receptor-associated kinase homologue in the Drosophila Toll pathway. Subsequent studies have revealed the central and non-redundant roles of mammalian Pellino-1, Pellino-2 and Pelino-3 in signaling pathways emanating from IL-1 receptors, Toll-like receptors, NOD-like receptors, T- and B-cell receptors. While Pellinos ability to interact with many signaling intermediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 114 publications
(203 reference statements)
0
53
0
Order By: Relevance
“…Instead, enhanced TLR4‐ or TLR7‐driven IRAK4‐mediated activation of MAPKs, NF‐κB and increased TNF‐α and CCL5 gene expression in macrophages from mice with lupus correlated with lower expression of Tollip and IRAK‐M, negative regulators of TLR signaling . In contrast, no significant changes in the mRNA levels of Pellino‐1 (positive) or Pellino‐3 (negative) regulators were observed, indicating the selective effect of lupus on expression of TLR regulators. IRAK‐M acts by preventing dissociation of IRAK1 from MyD88 or via inducing other negative regulators, such as A20, SHIP‐1, inhibitor of NF‐κB‐α , whereas Tollip suppresses IRAK1 activation .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Instead, enhanced TLR4‐ or TLR7‐driven IRAK4‐mediated activation of MAPKs, NF‐κB and increased TNF‐α and CCL5 gene expression in macrophages from mice with lupus correlated with lower expression of Tollip and IRAK‐M, negative regulators of TLR signaling . In contrast, no significant changes in the mRNA levels of Pellino‐1 (positive) or Pellino‐3 (negative) regulators were observed, indicating the selective effect of lupus on expression of TLR regulators. IRAK‐M acts by preventing dissociation of IRAK1 from MyD88 or via inducing other negative regulators, such as A20, SHIP‐1, inhibitor of NF‐κB‐α , whereas Tollip suppresses IRAK1 activation .…”
Section: Discussionmentioning
confidence: 89%
“…Since TLR responses are shaped by positive (Pellino‐1) and negative (Pellino‐3, Tollip, IRAK‐M) regulators , we determined the levels of these molecules in macrophages from lupus‐prone and lupus‐resistant mice. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, a bioinformatics analysis was performed to screen the potential targeting genes of miR-21 based on four prediction databases. Among the genes common to all four databases, we selected Peli1, a member of the RING finger E3 ubiquitin ligase family, as a target for further research because of its key role in various immune or inflammatory regulation pathways [28][29][30]. Liu et al [21] and Chang et al [22] reported that Peli1-deficient mice spontaneously developed SLE that was characterized by a severe lupus-like damage and autoantibody production.…”
Section: Discussionmentioning
confidence: 99%
“…E3 ubiquitin ligases have been reported to be involved in the regulation of RIG-I signaling (14,15). For example, E3 ubiquitin ligases TRIM25, Riplet, and MEX3C can mediate K63-linked polyubiquitination of human RIG-I (10,(16)(17)(18)(19), thus positively regulating RIG-I-mediated signaling.…”
mentioning
confidence: 99%